The Implementation of an A-P-O Framework-Oriented Approach Using Worksheets in Algebra Lessons to Enhance Students Conceptual Understanding - Taman, Ni Komang; Marsono, Marsono (International Journal of Multidisciplinary Sciences, 2025)
This research aims to (1) increase students understanding of mathematical concepts in learning Algebra material using the application of an approach oriented to the A-P-O framework by using worksheets, (2) to find out the application of the approach oriented to the A-P-O framework by using worksheets optimally, and (3) describes the level of response in the implementation of learning. This research involved 34 students. This type of research is classroom action research which is carried out in 3 cycles. The action is an approach oriented to the A-P-O framework using worksheet. Research data was collected using tests and questionnaires. Next, the data collected was analyzed using narrative statistics which will result in the research sharing that; (1) understanding of concepts in learning Algebra material is higher as long as understanding is less than good. This can be seen from the fact that the percentage of students who are classified as having a minimum level of understanding is quite good from cycle I, cycle II and cycle III, each meaning 76.45%; 82.34% and 88.22%, (2) application of an approach oriented to the A-P-O framework using optimal worksheets is by providing guidance or direction to students to dare to work and express ideas in their minds to create their own mathematical concepts; train students to present their work; creating an atmosphere so that students are able to interact in learning, (3) student responses in cycle I are quite positive while cycle II and cycle III are classified as positive.